Hypertension and Lipid Profiles in Middle-Aged Male Patients: A Study at a Tertiary Hospital in Surabaya, Indonesia - Nurtya, Arin; Tjempakasari, Artaria; Maimunah, Ummi; , Sulistiawati; Harsa, I Made Subhawa (Folia Medica Indonesiana, 2023)
Highlights: 1. Uncertainty regarding the association between hypertension and the levels of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) signifies the need for more research, particularly in the realm of sex-specific analysis. 2. Our study uncovered significant associations between hypertension and the levels of total cholesterol and triglycerides, expanding our understanding of the impact of lipid profiles on hypertension. 3. This research may potentially pave the way for personalized diagnostic and therapeutic strategies, ultimately enhancing hypertension management and patient outcomes. Abstract Hypertension is one of the most frequent non-communicable diseases and a risk factor for cardiovascular disease, contributing to most deaths globally. The risk of hypertension is higher in those with uncontrolled lipids. In this study, the incidence of hypertension and lipid profiles were examined from March 2020 to March 2022. The aim of this study was to determine the relationship between hypertension in men aged 45–60 years and their lipid profiles, which include total cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). This study used an analytical observational design with a cross-sectional approach. Medical records were utilized as secondary data. Statistical analysis was conducted using the Spearman rank correlation test. Statistical significance was determined at p<0.05. This research examined 115 patients with hypertension. The results showed that the stage of hypertension was correlated with total cholesterol (r=0.317; p=0.001) and triglyceride levels (r=0.217; p=0.02). However, the stage of hypertension was not significantly correlated with LDL (r=0.158; p=0.91) and HDL (r=0.75; p=0.423). Hence, this current study underscores the nuanced relationship between lipid profiles and the stage of hypertension in middle-aged male patients. This study highlights the importance of sex-specific analysis in hypertensive research. It also provides promising avenues for further investigation.